Anorectal Malformation with Rectovestibular Fistula and Vaginal Agenesis: Usage of Rectovestibular Fistula as a Neovagina Followed by PSARP with Preservation of the Anal Sphincter - Dessanti, Antonio; Louisma, Osnel; Pierre, Gabriel Steve; Liem, Nguhien Thanh (European Journal of Pediatric Surgery Reports, 2021)
Anorectal malformation with rectovestibular fistula associated with vaginal agenesis is rare. We report on a child in whom this combination was diagnosed at the age of 1 year. After creation of a divided descending colostomy, we chose to leave the rectum-rectovestibular fistula to function as a neovagina, while the sigmoid colon was relocated via modified posterior sagittal anorectoplasty. The colostomy was closed 6 months after the main surgery. After a follow-up of 3 years, the patient is continent for stool and urine. The introitus of the neovagina appears wide and easy to explore. We conclude that our surgical approach may be a good option for these children.
Keywords: anorectal malformation; vaginal agenesis; posterior sagittal anorectoplasty; vaginoplasty